Internet of Things Based Tidal Monitoring System at Kurnia My Darling Beach - Fachrid Wadly; Zuhri Ramadhan; Muslim; Dimas Alfisyahri Sitompul (Yayasan Sinergi Multidimensi Kreatif, 2024)
Internet of Things technology provides an effective solution to monitor real-time sea level changes remotely. This research aims to design and manufacture a sea level monitoring device based on NodeMCU ESP32 and HC-SR04 sensor where for 3 consecutive days the tide is monitored to exceed 130 cm above 10 am so that it has an impact on mangrove seedlings at Kurnia My Darling Beach. The results show that IoT-based sea level monitoring instrumentation tools have a high level of accuracy. The tool has been tested in real-time using ThingSpeak and can send notification notifications using WhatsApp. The results of monitoring for 3 days with this tool were obtained that the tide level exceeded the planted seedlings. It is hoped that in the future, this research will become a standard to make better tools that will be used for the purpose of monitoring mangrove seedlings so that the sustainability of mangrove forests can be maintained.